Livestock Business Development Strategies of Beef Cattle in Pangandaran District - Nuraeni, Cici; Sodiq, Akhmad; Setianto, Novie Andri; Setyaningrum, Agustinah; Widiyanti, Rahayu (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
The Pangandaran Regency in West Java has shown an increasing trend of beef cattle population over the past three years, reaching its peak of 18,938 in 2021, which indicates a potential opportunity for the development of beef cattle farming businesses. It is crucial to understand the key factors and strategies for this development. The study utilized a participatory survey method and the Harry King Nomogram technique to sample beef cattle farmers, collecting and analyzing the primary and secondary with descriptive, SWOT, and qualitative modeling analyses. The results showed that farmers in both lowland and highland areas were predominantly productive-aged. Performance metrics such as average service per conception and calving interval were observed at 14.48 and 2.37 in lowland areas, and 16.68 and 2.25 in highland areas, respectively. Key factors influencing the development of beef cattle farming in Pangandaran Regency included the availability of agricultural land, a supportive community environment, and effective breeding management. The SWOT analysis positioned both lowland and highland areas in quadrant I, suggesting that an aggressive growth-oriented strategy would be the most appropriate. Proposed strategies include increasing beef cattle population by optimizing agricultural land use, introducing technologies for processing forage feed and agricultural waste, aligning production with market demands through integrated farming practices, and implementing effective livestock waste management systems.